1978
DOI: 10.1039/f19787401538
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the hydrogen reduction of Ni2+ ions in X- and Y-zeolites

Abstract: NisNa 64H 6(sio2)1 O6(A102)8 6 Ni 3Na2 4 3 0 2 ) 3&4102)56 Ni20Na16(Si02) 136(402)56 Ni~1Na24(Si02)1o6(A102)s6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…This preference of Ni(II) for site SI has been verified by XRD and diffuse reflectance spectroscopy for synthetic NiNa-Y and nickel-exchanged natural faujasite. [32][33][34] For higher Ni loading, Ni occupation of site SI is limited by the number of such sites available and by its charge density which depends on the Si/Al ratio. It has been reported that in Na-Y with a Si/Al ratio of 2.4, out of 16 sites per unit cell a maximum of 12 SI sites are occupied by Ni(II) ions.…”
Section: Discussionmentioning
confidence: 99%
“…This preference of Ni(II) for site SI has been verified by XRD and diffuse reflectance spectroscopy for synthetic NiNa-Y and nickel-exchanged natural faujasite. [32][33][34] For higher Ni loading, Ni occupation of site SI is limited by the number of such sites available and by its charge density which depends on the Si/Al ratio. It has been reported that in Na-Y with a Si/Al ratio of 2.4, out of 16 sites per unit cell a maximum of 12 SI sites are occupied by Ni(II) ions.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the double peaks, Sr(0.068) sites have been unambiguously attributed to Ce3+ cations and Sr-(0.045) sites to Ni2+ cations. In fact the coordinates of Sp(0.068) sites Eire in good agreement with those found for Ce3+ ions in previous studies on Ce-X zeolites;6 in the same 5.3 (9) 5.9 (9) Ce(I'), X = Y=Z 0.068 (2) 0.068 (2) 0.066 (3) 0.069 (1) 0.067 (2) P 2.7(5) 3.8 (5) 5.5 (3) 4.4 (2) 5.4 (5) Ow(H')> X = Y = z 0.157 (4) 0.166 (2) 0.159 (3) P 10 (2) 17 (2) 18(2) ( ), X= Y=Z 0.202 (3) 0.191 (6) P 4.8 (7) 2.0 (6) Na(II), X = Y= Z 0.232 (1) 0.232 (1)…”
Section: Resultsmentioning
confidence: 99%
“…Long X-ray irradiation can result in a depopulation of the hexagonal prisms.11 On the other hand, in NiNa-X or -Y, Ni2+ cations prefer to occupy first sites S¡ and Sr, after complete dehydration. 1,4,11 The present work is concerned with the study of Ni2+ reduction in an X-type zeolite in the presence of La3+, a 0022-3654/80/2084-0875$01.00/0 © 1980 American Chemical Society particularly hydrophilic cation which could modify both the physicochemical properties of the zeolitic matrix and the Ni2+ cation location. Structural analysis was carried out on samples before reduction and with various degrees of reduction, simultaneously with the kinetic study of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…When relative absorbances of the CO and NO absorption bands against bulk metal concentration ratios were plotted, quantitative conclusions regarding surface concentrations could be made. This technique has several advantages over the more conventional spectroscopic techniques such as ESCA, SIMS, ISS, EXAFS, and AES in that (1) only the surface layer is sampled, (2) considerably more chemical information can 0022-3654/80/2084-0878801.00/0 be obtained, (3) when applied to highly dispersed supported bimetallic clusters, techniques such as ESCA and AES essentially sample the entire metal sample, and (4) infrared spectroscopy is inexpensive and can be used to sample the surface at high pressures under reaction conditions, Its major disadvantages are that (1) extensive preliminary experiments to determine surface interactions of adsorbing species are usually required, (2) the method is not as accurate as the above-mentioned spectroscopic techniques, and (3) surface reconstruction may be induced by the chemisorbing species.…”
Section: Introductionmentioning
confidence: 99%